Promoting Ekowisata-Agroforestry Berbasis Digital untuk Meningkatkan Sosio-Ekonomi Masyarakat di Desa Batu Putih Sekotong Lombok Barat - Zaini, Muh; utama, Lalu Wahyu putra; muhamad supriadi (Jurnal Pengabdian Masyarakat Bhinneka, 2022)
Batu Putih Village is one of several villages in West Sekotong. Geographically, this area is in a strategic location enriched with coastal areas and a series of hills. Like other areas in Sekotong, which are developing tourism potential based on the potential of existing villages, Batu Putih village is also developing as a tourist village by developing a tourism concept by designing a village with herbal plants. One of the concrete steps taken in optimizing the potential as well as accelerating the introduction of Batu Putih village into the wider community is a platform for promoting tourism that is being promoted by the local community. The service carried out by the Nurul Hakim Islamic Institute focuses on efforts to promote Batu Putih village and its efforts to improve the socio-economic community. Therefore, this research is entitled "Promoting Digital-Based Tourism to Improve Socio-economic Conditions in Bbatu Putih Village, Sekotong Barat. There are several keywords that need to be understood in the theme above, first is promoting efforts through digital platforms to improve the community's economy in the medium and long term, where the goal is that people can promote community-made products and introduce various types of tourism provided by Batu village. White. Second, the social dimension, which means that this service seeks to solve community problems in the social field by educating the community on an ongoing basis. As for the accomplishments of the service carried out for several months in Batu Putih village, there are several programs that have been carried out, including conducting community training in the form of introducing herbal plants and how to process them into finished product materials with economic value. Second, carry out discussions on how to manage and develop a good website by managing content to attract visitors. This activity is carried out together with servants and youth parties that focus on tourism development. Third, take part in reforestation activities involving the government, institutions, and community. This is one of the steps in preparing the village as well as preserving nature. fourth, by empowering mosque-based spiritual education that is carried out in a sustainable manner.